The changes of the ichthiofauna of river Berettyó and tributaries - Wilhelm, Sándor (Acta Agraria Debreceniensis, 2007)
In the spring and summer of 2005 I made ichtiologic research on the Barcau river in the area of Nusfalau – Saniob, as well as on its affluents.The results obtained were compared to those of the previous research performed on the Barcau river and partially on its affluents. Wenoticed a decrease of the fish lot both from the qualitative and the quantitative point of view, although the oil industry -the main source of pollution from this area – is in a temporary regress.Given the fact that upstream Suplacu-de-Barcau there are construction works for a dam and an artificiallakewhichwillinfluencetheriver fauna, the current research shall allow the repeat of the research and the comparison between the results, the identification of the effects of these works on the fish population from this area.